New approaches to HR-training: Hungarian experience - Kocziszky, György; Veres Somosi, Mariann; Pererva, P. G. (Хмельницький національний університет, 2024)
The report substantiates that the human resource management system in Hungary in the context of rapidly changing market conditions and toughening of the competitive environment can seriously affect corporate efficiency, which predetermines the need to achieve a high level of professionalism of HR managers and ensure the connection of HR management with business needs. Adaptation of foreign experience to the domestic personnel management system will contribute to the solution of these Tasks.
Нові підходи до підготовки HR-спеціалістів: досвід Угорщини
Keywords: human resources; personnel management; economic development; trends; technologies; transport enterprises